The role of lean training in lean implementation - Dinis-Carvalho, José (2020)
[Excerpt] Lean thinking was proposed by Womack & Jones (1996) as an interpretation of the way Toyota was successfully approaching its production system. The body of knowledge around the lean philosophy has been built over the years by practitioners and scholars from around the world and an interesting example of a conceptual model of lean tools and principles was proposed by Hodge et al (2011). The implementation of lean principles, concepts and tools is quite popular in many types of organization around the world but not always with success (Negrão, et al, 2017). Lean training is referred to frequently in the literature as playing an important role in the success of lean implementation and in continuous improvement programmes. Shrimali & Soni (2017) reported that one of the limitations observed for successful implementations of lean in SMEs was the poor training. Another study (Netland, 2016) shows that after management commitment and involvement comes training, and education as the most commonly reported critical success factor in the improvement programme literature. Similar results were also reported by Yamchello et al (2014). Lean in education and training can be divided into two distinctive areas of knowledge and work. One area can be called Lean Teaching and the other area can be called Teaching Lean. The Teaching Lean area can be described as the way students and professionals can be effectively trained on Lean principles, concepts and tools so they can apply Lean in real contexts such as factories and other organizations. This area is quite a large subject with fast growing interest in recent years. The other area, Lean Teaching, can be described as how lean principles and concepts can be effectively applied in learning/training activities. There is a very interesting book on the subject published by Emiliani (2015) but this subject remains little explored by academic authors with very few articles published. Another closely-related area sometimes with confusing interpretation as Lean Teaching is the use of lean in schools and universities. In these cases the use of Lean is mainly applied in offices and other service areas that exist in academic organizations. [...]